REMEDIASI MISKONSEPSI DENGAN MODEL WONDERING EXPLORING EXPLAINING BERBANTUAN TIK MATERI GERAK LURUS DI SMAK - Sopaba, Alosio Helmy; Tandililing, Edy; B. Arsyid, Syaiful (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the effect of giving learning materials to remediate students' misconceptions on straight-moving material change regularly in class X SMAK Abdi Wacana Pontianak. The method used is pre experimental Design with the design of One Group Pretest Posttest Design. The sample used in this study amounted to 24 students of SMAK Abdi Wacana Pontianak academic year 2017/2018 who were selected using purposive sampling technique. The data collection tool used is a multiple choice test with an open reason consisting of 10 questions. The results showed that the average percentage of students who experienced misconceptions decreased by 30%. McNemar test results obtained on average 2 Calculate (12.3) ˃ χ2Table (3.84) for db = 1 and α = 5% so that there was a significant conceptual change after remediation using the Wondering Learning Model - Exploring- Explaining Assisted Media Technology Information and Communication. The result of the effect size is obtained, which is 3.9 (high category). The results of this study are expected to be used as an alternative remediation activity for students who have learning difficulties Keywords: Wondering - exploring- explaining, information and communication technology, straight motion.